2022
DOI: 10.1007/s10571-022-01238-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional Two-Way Crosstalk Between Brain and Lung: The Brain–Lung Axis

Abstract: The brain has many connections with various organs. Recent advances have demonstrated the existence of a bidirectional central nervous system (CNS) and intestinal tract, that is, the brain-gut axis. Although studies have suggested that the brain and lung can communicate with each other through many pathways, whether there is a brain–lung axis remains still unknown. Based on previous findings, we put forward a hypothesis: there is a cross-talk between the central nervous system and the lung via neuroanatomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 85 publications
0
31
0
Order By: Relevance
“…In addition, we did not specifically identify which nuclei in the ventral medulla are more important for lung tumor progression, and the regulatory mechanisms of these nuclei on lung function have not been investigated. Previous studies have shown that the medullary vagal efferent nerves can participate in neuroimmunoregulation by releasing acetylcholine to peripheral lung tissue [ 18 ]; however, whether these neurotransmitters affect lung tumors remains to be verified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we did not specifically identify which nuclei in the ventral medulla are more important for lung tumor progression, and the regulatory mechanisms of these nuclei on lung function have not been investigated. Previous studies have shown that the medullary vagal efferent nerves can participate in neuroimmunoregulation by releasing acetylcholine to peripheral lung tissue [ 18 ]; however, whether these neurotransmitters affect lung tumors remains to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…A paper published in Nature in 2022 also revealed the existence of brain–lung axis and proposed that the imbalance of lung microbiota would significantly affect the autoimmune response of the central nervous system [ 17 ]. Among them, the brain–gut axis and the brain–lung axis are bidirectional pathways between the central nervous system and the periphery, involving the crosstalk of the neuroanatomical pathway, immune pathway, endocrine pathway, and microbial pathway [ 18 ]. The autonomic nervous system is a neuroanatomical pathway for two-way communication between the central and peripheral regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been scattered evidence in the literature for brain-lung relationships, across the spectrum of respiratory disorders. 15 , 16 , 17 , 18 , 19 , 20 Pulmonary fibrosis in particular has been clinically associated with cognitive decline, 13 , 21 increased risk of neurodegenerative disorders, 14 , 21 cerebrovascular accidents, 22 and a high prevalence of anxiety (30–50%) and depression (about 20–30%). 23 However, the mechanisms linking IPF to brain changes and dysfunction are poorly understood and likely multifactorial; including either direct shared pathomechanisms that result in fibrosis and scar development in the lung and to altered brain development and accelerated neurodegeneration or indirect sequelae of brain injury resulting from fibrosis-associated hypoxic tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the brain and lung can communicate through a variety of ways, such as neuroanatomical pathway, endocrine pathway, and immune pathway etc. 11 The lung is an organ that contains microbiota 12 . The microbial community in the lung composes of about 140 distinct families, while most of their functions in healthy individuals are still unknown 12 .…”
Section: Introductionmentioning
confidence: 99%